2012
DOI: 10.1074/jbc.m111.280768
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 34c Gene Down-regulation via DNA Methylation Promotes Self-renewal and Epithelial-Mesenchymal Transition in Breast Tumor-initiating Cells

Abstract: Background:The mechanisms for miRNA dysregulation in BT-ICs remain obscure. Results: Single hypermethylated CpG site in the promoter region of miR-34c gene repressed miR-34c expression by reducing DNA binding activities of Sp1 and promoted self-renewal and EMT of BT-ICs. Conclusion: Single hypermethylated CpG site in the promoter region contributes to the reduction of microRNA in BT-ICs. Significance: Methylation regulates the expression of microRNA in BT-ICs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(123 citation statements)
references
References 44 publications
3
118
0
Order By: Relevance
“…29 Numerous studies have shown the dysregulation of miR-34 in various types of cancers, including hepatocellular, mesothelial and colon cancer, melanomas, leukemia, nasopharyngeal cancer, 30 prostate cancer, 31 neuroblastomas, 32 glioblastoma 33 and breast cancer. 34 Yet, little research has been conducted in EC, apart from a functional study by Li et al 35 demonstrating that miR-34c acts as a tumor suppressor in HEC-1-B cells, and that E2F3 protein may be a target of miR-34c.…”
Section: Discussionmentioning
confidence: 99%
“…29 Numerous studies have shown the dysregulation of miR-34 in various types of cancers, including hepatocellular, mesothelial and colon cancer, melanomas, leukemia, nasopharyngeal cancer, 30 prostate cancer, 31 neuroblastomas, 32 glioblastoma 33 and breast cancer. 34 Yet, little research has been conducted in EC, apart from a functional study by Li et al 35 demonstrating that miR-34c acts as a tumor suppressor in HEC-1-B cells, and that E2F3 protein may be a target of miR-34c.…”
Section: Discussionmentioning
confidence: 99%
“…The hypermethylation of promoter CpG islands has been found to affect not only tumor-suppressor mRNAs, but also tumor-suppressor miRNAs. Several tumor-associated miRNAs have been reported to be silenced by the aberrant hypermethylation of their promoter regions in breast cancer, including miR-124, miR-34c, miR-148a, miR-155, miR-203 and miR-129 (3,(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence shows that miRNAs can regulate TICs, and aberrant miRNAs in TICs may help in the understanding the mechanism of tumorigenesis, therapyresistance, recurrence, and metastasis (Yu et al, 2010;Wu et al, 2012;Yu et al, 2012;Kwon and Shin, 2013). miR-155 plays an important role in various physiological and pathological processes (Faraoni et al, 2009;Elton et al, 2012) and has been found to be upregulated in several solid tumors, such as clear-cell kidney cancer (Juan et al, 2010), hepatocellular carcinoma (Wang et al, 2009a), breast cancer (Jiang et al, 2010;Kong et al, 2010), pancreatic cancer (Habbe et al, 2009;Greither et al, 2010;Ryu et al, 2010), and lung cancer (Yanaihara et al, 2006;Donnem et al, 2011).…”
Section: Discussionmentioning
confidence: 99%